Low carbon supply chain firm integration and firm performance in China. (1st June 2017) - Mao, Zhaofang; Zhang, Shan; Li, Xiaomei
Abstract: Based on the natural resource-based view (NRBV), this paper analyzes the relationship between internal low carbon integration and external low carbon integration and firm performance, as well as the moderating role of quality management within low carbon supply chain, by researching 12 business departments of machinery, electronic, and transportation components industries in China. The results of this empirical study show that internal low carbon integration helps to improve firm's environmental performance, while hinder firm's financial performance. External low carbon integration improves both environmental performance and financial performance. In the meanwhile, quality management strengthens positive relationships that found in this study and weakens the negative relationship between internal low carbon integration and financial performance.